Performance and sulphur and zinc utilization by maize (Zea mays L.) as influenced by integrated nutrient management - Joshi, Ekta Joshi; Nepalia, V.; Verma, Arvind; Singh, Dilip; Sharma, S.K. (Annals of Agricultural Research, 2014)
The experiment was conducted at Udaipur to study the performance and sulphur, zinc utilization by PEHM-2 under influence of integrated nutrient management. The study showed that the combined application of recommended dose of NPK with 10 tonnes/ha farm yard manure resulted in higher grain yield (4075 kg/ha) of maize compared to the application of either only inorganic fertilizer, organic sources or 50% higher dose of recommended dose of inorganic fertilizers. The integrated nutrient management resulted in better uptake of sulphur and zinc at different growth stages and less losses of nutrients from soil.